Compensatory Growth Response and Feed Intake Pattern of Indian Major Carps in Confined Aquatic Environment - MOHANTY, R K; THAKUR, A K; NAYAK, A K; AMBAST, S K (Journal of the Indian Society of Coastal Agricultural Research, 2020)
Effects of feed restriction on compensatory growth (CG) performance of Indian major carps and their feed intake pattern in a grow-out production system were examined. In this experiment it was found that the magnitude of CG depended on the duration of feed deprivation and the fish deprived and refed cyclically had higher feed intake than that of the control fish, with significantly improved feeding efficiency, during the refeeding periods. This condition along with hyperphagia and improved feed conversion efficiency also helped in the occurrence of CG. Higher performance index (168-174), PSI (240.3-321.2), compensatory growth index (>100%) and per day increment (1.68-2.1) enhanced the overall survival rate (94.3%) and yield (2.86 t ha-1). This infers that occurrence of CG has the potential to enhance growth, productivity and minimize feed input which in turn maintains water quality.